Tacrolimus-induced epilepsy with primary membranous nephropathy: A case report. Issue 9 (5th March 2021) - Yang, Yan; Zhang, Lei; Mo, Ying; Ren, Rong; Wang, Fengmei
Abstract: Rationale: Tacrolimus-associated neurologic disorders can be found in some cases, mainly in organ transplantation patients. However, epilepsy induced by tacrolimus in primary membranous nephropathy (PMN) patient is scare. Patient concerns: A 63-year-old man experienced 1-year history of foamy urine, and edema of lower extremity. Diagnosis: The patient had proteinuria, hypoalbuminemia, which indicated nephrotic syndrome. Further, we performed renal biopsy for this patient. Combined with the renal biopsy result, the diagnosis of primary membranous nephropathy was established. Intervention: At first, irbesartan was administrated for 6 months. However, the proteinuria had no obvious improvement. Tacrolimus was administrated afterwards. Outcomes: Twenty-two days after tacrolimus treatment, epilepsy occurred. Sodium valproate and carbamazepine were successively given to control epilepsy. However, the epileptic symptoms were not effectively controlled. During the treatment, the concentration of tacrolimus fluctuated greatly. At last, levetiracetam was given to maintain the curative effect. Fortunately, the patient did not suffer from epilepsy again. The concentration of temporary tacrolimus was stable, whereas proteinuria gradually decreased. Lessons: Tacrolimus-induced epilepsy should be considered in patients exhibiting acute neurological symptoms. Early diagnosis and effective treatment play a vital role for favorable prognosis.